2019
DOI: 10.1158/1535-7163.mct-19-0150
|View full text |Cite
|
Sign up to set email alerts
|

COMMD3:BMI1 Fusion and COMMD3 Protein Regulate C-MYC Transcription: Novel Therapeutic Target for Metastatic Prostate Cancer

Abstract: Gene rearrangement is reported to be associated to the aggressive phenotype and poor prognosis in prostate cancer. We identified a gene fusion between a transcription repressor (BMI1) and transcriptional factor (COMMD3) in human prostate cancer. We show that COMMD3:BMI1 fusion expression is significantly increased in prostate cancer disease in an order: normal tissue < primary < metastatic tumors (Mets). Although elevated TMPRSS-ERG/ETV fusion is reported in prostate cancer, we identified a subtype of Mets exh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…The role of DNAJC1, COMMD3 and SPAG6 in MLLT10 r acute leukemia is yet to be investigated, but both COMMD3 and SPAG6 have implicated roles in other malignancies. COMMD3 levels are elevated in prostate cancer, and have been demonstrated to upregulate C‐MYC expression, promoting proliferation in prostate cancer models 74 . SPAG6 is a member of the cancer‐testis antigen family primarily involved in regulation of the microtubule system, with secondary roles associated with inhibition of the Akt and p53 pathways 75 .…”
Section: The Role Of Mllt10 In Mllt10r‐mediated Leukemogenesismentioning
confidence: 99%
“…The role of DNAJC1, COMMD3 and SPAG6 in MLLT10 r acute leukemia is yet to be investigated, but both COMMD3 and SPAG6 have implicated roles in other malignancies. COMMD3 levels are elevated in prostate cancer, and have been demonstrated to upregulate C‐MYC expression, promoting proliferation in prostate cancer models 74 . SPAG6 is a member of the cancer‐testis antigen family primarily involved in regulation of the microtubule system, with secondary roles associated with inhibition of the Akt and p53 pathways 75 .…”
Section: The Role Of Mllt10 In Mllt10r‐mediated Leukemogenesismentioning
confidence: 99%
“…In the light cyan module, Extl2 (Exostosin-like 2) codes for a glycosyltransferase from the exostosin family that modifies the heparin sulfate structure and is involved with breast cancer cell adhesion and invasion [ 16 ]. In addition, the hub gene Commd3 (COMM domain-containing 3) was shown to regulate c-myc transcription and prostate tumor growth in mice [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the light cyan module, Extl2 (Exostosin-like 2) codes for a glycosyltransferase from the exostosin family that modifies the heparin sulfate structure and is involved with breast cancer cell adhesion and invasion [16]. In addition, the hub gene Commd3 (COMM The functions, pathways, and histone marks were considered to be significantly enriched if their adjusted p values were less than 0.05 domain-containing 3) was shown to regulate c-myc transcription and prostate tumor growth in mice [17]. The red, salmon, turquoise, and magenta modules were positively correlated with EMT (Fig.…”
mentioning
confidence: 99%
“…Fusion genes are a class of oncogenes that have been found in many cancer types including PCa and caused by genomic rearrangements [36]. Gene fusion between a transcription repressor (BMI1) and a transcriptional factor (COMMD3) has been recently identified in PCa, which triggers disease recurrence and poor survival [37]. It was reported that targeting the COMMD3:BMI1 fusion gene with siRNA leads to reduced c-MYC expression and decreased tumor cell proliferation both in vitro and in metastatic tumors in a xenograft mouse model of PCa [37].…”
Section: Sirna-mediated Cancer-associated Gene Silencing In Prostate Cancermentioning
confidence: 99%